Eco-friendly bench-scale zeolitization of an Al-containing waste into gismondine-type zeolite under effluent recycling. (10th September 2017) - Sánchez-Hernández, Ruth; Padilla, Isabel; López-Andrés, Sol; López-Delgado, Aurora
Abstract: The feasibility of developing an eco-friendly bench-scale zeolitization process of NaP1 from an Al-containing waste and under recycling of effluents was evaluated. Prior lab-scale tests were performed to optimize the synthesis conditions. The mixture of effluents, i.e., mother liquors (ML) from the synthesis and rinse water (RW) from the cleaning step of the zeolites, was recycled several times to study the reduction of raw materials (NaOH and water) and accordingly the reduction of costs. The bench-scale process allows the complete transformation of the waste into NaP1 zeolite, reaching equivalent reaction yields (2.5 ton of zeolite per ton of waste) to the lab-scale process and avoiding the generation of new solid residues. The effect of the recycling of effluents on the physical-chemical properties of the resulting zeolites was investigated. NaP1 zeolite was the only crystalline phase obtained, showing morphological, textural and crystalline characteristics closely similar to NaP1 synthesized from fresh NaOH aqueous solutions and from pure chemical reagents. NaOH and water consumption savings of 80 and 67%, respectively, were obtained, representing a cost reduction around 70%. These results show that the bench-scale process to obtain NaP1 from an Al-waste with recycling of effluents can be a more sustainable alternative compared with the traditional synthesis methods. Graphical abstract: Highlights: Bench-scale zeolitization of NaP1 from Al-waste developed with effluents recycling. Green and feasible process to obtain zeolites involved zero-waste discharge. Significant savings in the consumption of raw materials were achieved.